# Answer to Question #7490 in Differential Equations for noor

Question #7490

Solve differential equation

-xdy/dx+6y=3x(y^4)^1/3

-xdy/dx+6y=3x(y^4)^1/3

Expert's answer

First you need to divide every term in the equation by x:

y'+6/x*y=3y^(4/3)

This equation is often called Bernoulli differential equation. You can find here more sufficient information about it and how to solve it.

Then we divide every term of the equation by y^(4/3):

y^(-4/3)*y'+6/x*y^(-1/3)=3

Now we make a substitution z=y^(-4/3+1)=y^(-1/3) => y=1/z^3, y'=-3/z^4 *z'

So we obtain

-3/z^4*z'*z^4+6/x*z=3

-3z'+6z/x=3

z'-2z/x=-1

z(x)=Cx^2-x

So y=1/z^3=1/(Cx^2-x)

y'+6/x*y=3y^(4/3)

This equation is often called Bernoulli differential equation. You can find here more sufficient information about it and how to solve it.

Then we divide every term of the equation by y^(4/3):

y^(-4/3)*y'+6/x*y^(-1/3)=3

Now we make a substitution z=y^(-4/3+1)=y^(-1/3) => y=1/z^3, y'=-3/z^4 *z'

So we obtain

-3/z^4*z'*z^4+6/x*z=3

-3z'+6z/x=3

z'-2z/x=-1

z(x)=Cx^2-x

So y=1/z^3=1/(Cx^2-x)

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment